Julien Pharo, Démocratie d’entreprise et fiscalité. Enjeux théoriques et pratiques de la mise en place d’une fiscalité incitative procédurale - Julien Pharo (Revue de la Régulation)
This thesis, which is primarily concerned with economic theory, proposes to consider, from a pragmatist and institutionalist point of view, the possibility that tax incentives for companies might have the objective of democratising their organisation. The aim is to develop a concept of procedural incentive taxation (PIT), which would, on the one hand, break out of the peculiarities of current tax systems and, on the other hand, contribute to the democratisation of business in a way that complements other regulatory tools. The PIT is therefore based on the project of transforming the organisational structure of the company in an ethico-political sense by encouraging the deployment of practical reason, as opposed to the instrumental incentive taxation (IIT) which only targets the results of behaviour, and in particular market prices, with the indirect effect of reinforcing the predominance of instrumental rationality within the company. This thesis has enabled us not only to re-examine the possibility of public action to democratise business, but also to question the meaning of tax incentives from the point of view of the public authorities. With a view to differentiating between companies from a fiscal point of view and conditioning public aid on this basis, it has led us to formulate multidimensional criteria for evaluating companies according to their commitment (or otherwise) to democratisation processes.